Body mass index and its correlation with polycystic ovarian syndrome: Insights from a cross-sectional study among MBBS females at a tertiary care hospital. - Moutam, Shailaja; Hasamnis, Dr. Varada A.; Vijaya, Chaganti (Student's Journal of Health Research Africa, 2025)
Background: Polycystic ovarian syndrome (PCOS) is a multifactorial endocrine disorder with rising global prevalence among reproductive-aged women. Body Mass Index (BMI) plays a significant role in modulating its clinical presentation. Objectives: To evaluate the correlation between BMI and PCOS prevalence and to determine the impact of BMI on clinical and anthropometric features among female medical students. Methods: A cross-sectional observational study was conducted at the Konaseema Institute of Medical Sciences and Research Foundation, Amalapuram, from November 2023 to November 2024. Two hundred female MBBS students aged ≥18 years were enrolled. PCOS was diagnosed using the Rotterdam criteria. Anthropometric parameters, including BMI, waist/hip ratio, and mid-arm circumference, were recorded, and clinical features such as hirsutism (mFG score), acne, alopecia, and acanthosis nigricans were assessed. Statistical analysis was performed using SPSS version 22. Results: The mean age of participants was 23.7 ± 3.6 years, with most belonging to the 18–25 year age group. Among 200 students, 74 (37%) were diagnosed with PCOS. The mean BMI, waist/hip ratio, mFG score, and mid-arm circumference were significantly higher in PCOS individuals. A high waist/hip ratio (>0.85) was seen in 70.2% of PCOS participants versus 33.3% of non-PCOS participants. Prevalence was greatest in obese individuals (BMI ≥30 kg/m²), with features including menstrual irregularities, hirsutism (17.9% vs. 5.0%, p = 0.025), alopecia, and polycystic ovarian morphology. Some lean participants (BMI 18.5–24.9 kg/m²) also manifested PCOS, suggesting additional contributing factors. Conclusion: The prevalence of PCOS in this cohort was 37%, indicating a considerable burden among young female medical students. Increased BMI correlated strongly with PCOS severity, though normal-weight individuals also exhibited features, highlighting the roles of genetic and metabolic factors. Recommendations: Routine BMI screening and lifestyle interventions are essential for reproductive-aged women, irrespective of BMI, to reduce PCOS-related complications and long-term risks.